Importance of Expediting Ambulance Cross-Border Operations in the El Paso-Ciudad Juarez Bi-national Region. (June 2017) - Salgado, David; Aldrete, Rafael M.; Martin, Peter T.; Qureshi, Ihtesham; Rodriguez, Gustavo J.
Abstract : Background: The El Paso (U.S.)-Ciudad Juarez (Mexico) bi-national region has a population of approximately 2.5 million and thousands of people who commute daily across borders for work, shopping, and family visits. As a result of the high daily commuting activity, it is not uncommon for U.S. residents to face the need of emergency medical transportation to a hospital in El Paso as a result of a sudden medical condition (e.g. stroke or heart attack). These patients are currently transported from Mexico to a U.S. hospital through one of the Ports of Entry (POEs) that connect these two cities. However, current regulations do not allow Mexican ambulances to operate in the U.S. Therefore, Mexican ambulances must wait in line with the rest of passenger vehicles trying to enter into the U.S. Once at the border, a U.S. Customs and Border Protection (CBP) officer check the patient's information, and calls El Paso Fire Department (EPFD) requesting an ambulance to pick up the patient at the POE. This lengthy process along increasing wait times at the POEs and traffic congestion levels in Ciudad Juarez significantly delay the patient's arrival to the U.S. hospital. Methods: EPFD receives around 400 emergency calls every year from CBP officers at POEs requesting an ambulance. EPFD prospectively collect data about dispatch calls, time of the call and types of patients transported according to medical and trauma conditions. Data from March 2011 to September 2015 were analyzed, a descriptive analysis was performed based on the year, month, and day of the week or time of the day and patient condition. Results: The number of emergency calls at the El Paso-Ciudad Juarez POEs has steadily increased over time, going from 178 in 2011 to 479 in 2014, an increase of 270% in three years. Approximately one third of all calls were made during weekends. In 2011, 2012, 2013 and 2014 the EPFD received a total of 13, 42, 37 and 26 weekend calls reporting patients in critical conditions respectively. Conclusions: The number of patients that need to be transported from Ciudad Juarez to El Paso to receive emergency care has grown every year since 2011. Current transportation practices require a significant amount of time and time plays a vital role in the recovery of critical condition patients. There is a need of an agreed upon ambulance cross border operations protocol among all parties involved that expedites the overall transportation process.